Polycyclic Aromatic Hydrocarbons in Urban Stream Sediments - Jejal Reddy Bathi; Robert E. Pitt; Shirley E. Clark (Advances in Civil Engineering)
Polycyclic aromatic hydrocarbons (PAHs) are persistent organic pollutants of high environmental concern with known carcinogenic activity. Although literature documents PAH fate in urban runoff, little is known about their distribution on sediment sizes, which is essential for determining their treatability and fate in receiving waters. This paper has quantified the concentrations of selected PAHs in urban creek sediments and examined possible relationships between sediment PAH content and sediment characteristics, such as particle size, volatile organic content (VOC), and sediment chemical oxygen demand (SCOD). SCOD, VOC, and PAH concentrations of sediments showed a bimodal distribution by particle size. The large diameter sediments had the highest VOC and also had the highest PAH concentrations. The spatial variation of PAH content by sediment sizes also was statistically significant; however, the mass of the PAH material was significantly affected by the relative abundance of the different particle size classes in the sediment mixtures.